Strategi Peningkatan Motivasi Dan Kepuasan Kerja Pada Guru Sekolah Dasar Negeri 2 Kopen Kecamatan Jatipurno Tahun 2025 - Paryanti Paryanti; Baidi Baidi (Journal of Innovative and Creativity, 2026)
This study investigates effective strategies to improve the motivation and job satisfaction of elementary school teachers working in rural settings, with a particular focus on SD Negeri 2 Kopen, Jatipurno District. The research adopts a qualitative approach using a phenomenological design. Data were gathered through in-depth interviews, classroom observations, and document reviews involving eight teachers with varying professional backgrounds and experiences. The results indicate that teachers maintain a high level of motivation and job satisfaction, even amid limited infrastructure and resources. Intrinsic factors play the most crucial role in shaping teachers’ enthusiasm and satisfaction—especially the sense of purpose in their profession, moral commitment to students, and the spiritual values that drive their dedication to teaching. Additionally, supportive leadership from the principal and positive social interactions among colleagues foster a conducive and collaborative work environment, enhancing teachers’ emotional attachment to their institution. In contrast, extrinsic aspects such as financial compensation and physical facilities were perceived as less adequate but did not significantly reduce teachers’ motivation or work commitment. These outcomes align with both classical and modern motivation theories, including Herzberg’s Two-Factor Theory, Self-Determination Theory (Deci & Ryan), and Maslow’s Hierarchy of Needs. Each emphasizes that motivation and job satisfaction are grounded in fulfilling essential psychological needs—autonomy, competence, and relatedness—alongside achieving meaning and self-actualization within one’s profession. Consequently, this research suggests the need for supportive and participatory leadership, a collaborative school culture, and ongoing professional development programs as key strategies to sustain and strengthen teachers’ motivation and job satisfaction in rural elementary education.